Uma arquitetura orientada a serviços para visualização de dados em dispositivos inteligentes - SILVA JUNIOR, Jairo de Jesus Nascimento da (Universidade Federal do Pará, 2017)
Technological developments of smartphones and tablets, the great amount of electronic stored information and the need for decision-making, individually or collaboratively, anywhere and anytime, demands the conception and development of services for data visualization. The Internet has played an important role as a knowledge-sharing network and in this context, some service oriented architecture (SOA) applications have emerged in all kind of study fields. Therefore, this work aims the conception and development of a service aggregation that will favor ubiquity and pervasiveness in data visualization applications, allowing users to build domain-specific data visualizations in an easy and intuitive way. With this kind of service, it is possible to build data visualization applications for different smart devices such as smartphones, tablets, desktop, smart TV's, etc. A Web API that supports the main characteristics of an information visualization tool in different platforms reaches this abstraction. REST (REpresentational State Transfer) Style was employed in the service conception as the architectural communication model. Client-side and server-side applications were developed using Java with a data visualization generator engine called PRISMA. As a use case, was developed a client Android application in order to test the created services. Lastly, initial data about usability essays performed in the developed application will be presented.